Implementasi Pendidikan Multikultural dalam Pembelajaran: Studi Kasus di SD Negeri Rejoagung 2 Jombang - Anam, Choirul; Marlina, Tuti (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The country of Indonesia has Unity in Diversity guidelines which means "different but still one too". In avoiding the conflicts that occur, it is necessary to instill multicultural behavior in the midst of society. The most effective inculcation of multicultural behavior is through the world of education, in this case through the application of multicultural education. Multicultural education aims to create harmony in students so that students can understand the differences that occur with others so that it is hoped that differences in harmony between religious communities can be realized. The objectives of this study are: (1) To determine the planning carried out to realize multicultural education in students (2) To determine the process of implementing multicultural education in student teaching and learning activities (3) To find out the process of implementing multicultural education in learning evaluation. The results of this study indicate that (1) a multicultural education plan was created from the results of organizing school institutions that mutually design and also build a foundation seen from existing religious differences (2) Implementation of multicultural education at SD Negeri Rejoagung 2 Ngoro can be seen from a multicultural school environment, the application of multicultural education through formal and non-formal education and inter-religious harmony that has long occurred in the Rejoagung community (3) Evaluation carried out in multicultural education at SD Negeri Rejoagung 2 Ngoro Ngoro seen from perception, understanding, appreciation , the actions and attitudes of students who can appreciate the diversity and differences that occur.